The genesis of a sculpture (Northbrook, Ill. Roland Collection, 1986)
Employs a fascinating technique to show the various stages of a sculpture produced by Maxim Adam-Tesier.
VHS format.
Directors, Oliver Clouzot, Julen Pappe ; music, Anton Webern.
Keywords: Sculpture